2019
DOI: 10.1016/j.chb.2018.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy and acceptance of robots

Abstract: As many post-industrial societies are rapidly ageing, intelligent and innovative solutions from the technology side are sought to ensure that welfare services continue in the future. Both social and nonsocial assistive robots are considered as solutions. To ensure the successful implementation of new technology, it is essential to understand the factors that influence the user's decision to accept or reject technology. The aim of this study was to understand the association between robot use self-efficacy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 54 publications
8
63
0
4
Order By: Relevance
“…However, this factor has a significant effect on behavioural intention of females in the US, which contradicts with our hypothesis. This shows that female employees in the US find self-confidence in undertaking the steps required to ensure the security of their smartphones as an important factor, which is consistent with the findings of He and Freeman (2010) and Latikka et al (2019). This is linked to the knowledge ad awareness of the recommended security behaviour.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, this factor has a significant effect on behavioural intention of females in the US, which contradicts with our hypothesis. This shows that female employees in the US find self-confidence in undertaking the steps required to ensure the security of their smartphones as an important factor, which is consistent with the findings of He and Freeman (2010) and Latikka et al (2019). This is linked to the knowledge ad awareness of the recommended security behaviour.…”
Section: Discussionsupporting
confidence: 87%
“…Self-efficacy is one of the key aspects of human activity, including interaction with technology and security (Latikka, Turja, & Oksanen, 2019). Previous studies showed that males are generally more confident with the use of technology than females (He & Freeman, 2010).…”
Section: Self-efficacymentioning
confidence: 99%
“…There, the doll is an object upon which we project ourselves, but robots are seen as subjects (Turkle 2011). Latikka et al (2019) examine robot acceptance in general and show that men are more accepting than women, younger people more so than their elders, and that people with more experience with technology are also more prone to accept robots. There are differences between different kinds of robots, however, and it seems that industrial robots are easier to accept than, for example, care robots (Savela et al 2018;Latikka et al 2019).…”
Section: Robots As Partnersmentioning
confidence: 99%
“…同样作为一种跨情境的稳定个体特质, 个体创 新性(personal innovativeness)主要是指个体愿意尝试新 科技 [85] , 它与人们对人工智能的接受度也密切相关 [86] . 此外, 使用者的自我效能(self-efficacy) [87] 等心理学因素 同样会对机器人接受度产生影响. 自我效能的作用主 要体现在还未完全掌握使用机器人技能的新手身上.…”
Section: 拟人化是在机器人外观研究中最为热点的一个问题unclassified
“…Latikka等人 [87] 的研究发现, 被试使用机器人的自我效 [80] . 个体 具有人-机器人交互的经验能够增加机器人的可及 性 [88] , 而缺乏这种经验则会导致人们面对机器人时的 不确定感 [89] .…”
Section: 拟人化是在机器人外观研究中最为热点的一个问题unclassified